Strategi Pengembangan Agribisnis Kentang (Solanum tuberosum L.) di Kabupaten Brebes - khusnul khatimah; Wahyu Febriyono (Universitas Medan Area, 2021)
Brebes Regency is the third largest potato producer in Central Java. Potatoes have decreased production growth, but the amount of demand is increasing. In fact, the highlands of Brebes Regency have the potential for potatoes agribusiness. The purpose of this study to analyze the internal and external factor, and formulate the development strategy of potatoes agribusiness in Brebes Regency. Respondents consisted of potato farmers, stakeholder, and key person through in-depth interview. The internal and external factor are identified using the IFE and EFE matrix. The combination of it are used as a basis of the preparation of alternative strategies with IE and SWOT matrix by considering stakeholder and key person. The result showed that potatoes agribusiness in Brebes Regency is in a position to grow and build (cell I). The alternative strategies divided into 4 strategic groups; S-O, S-T, W-O, and W-T. The strategic priority is in the S-O strategy.